Die Suid-Afrikaanse Oorlogsekonomie gedurende die Tweede Wêreldoorlog - deel II - Vd B. Breedt, J. (Scientia Militaria - South African Journal of Military Studies, 2012)
For a short English summary of the contents of this article, please see part one of the article in Militaria 13/1 of 1983.